Using Evidence in Policy and Practice Lessons from Africa - Goldman, Ian; Pabari, Mine (Taylor & Francis, 2020)
"This book asks how governments in Africa can use evidence to improve their policies and programmes, and ultimately, to achieve positive change for their citizens. Looking at different evidence sources across a range of contexts, the book brings policy makers and researchers together to uncover what does and doesn't work and why. Case studies are drawn from 5 countries and the ECOWAS (west African) region, and a range of sectors from education, wildlife, sanitation, through to government procurement processes. The book is supported by a range of policy briefs and videos intended to be both practical and critically rigorous. The book uses evidence sources such as evaluations, research synthesis or citizen engagement, to show how these cases succeeded in informing policy and practice. The voices of policy makers are key to the book, ensuring that the examples deployed are useful to practitioners and researchers alike. This innovative book will be perfect for policy-makers, practitioners in government and civil society, and researchers and academics with an interest in how evidence can be used to support policy making in Africa."